Pengaruh Kondisi Sosial Ekonomi Keluarga Dan Motivasi Belajar Terhadap Minat Melanjutkan Studi Mahasiswa Angkatan 2022. - Dafit Makalalag; Muhammad Amir Arham; Sri Endang Saleh; Sudirman Sudirman (State University of Gorontalo, 2023)
This research employed a quantitative approach with the Ex-post facto research method. The data used were primary data obtained by distributing questionnsires to economics education students in the class of 2022, with a total sample of 70 respondents. At the same time, the data analysis technique technique used was multiple linear regressions. The results of data analysis and discussion denoted that family socioeconomic status and learning motivation had a positive and significant effect on interest in pursuing education. This result signified that good family socioeconomic status and learning motivation could increase students’ interest in pursuing education at the department of economics education, faculty of economics, universitas negeri gorontalo. It could be concluded that the research finding could answer the problems formulated in this research.